High expression levels of bone morphogenetic protein-2 and p-glycoprotein related with progressivity in patient with osteosarcoma - Kawiyana, Ketut Siki; Handoyo, Henry Ricardo; Wiratnaya, I Gede Eka; Suyasa, I Ketut; Ridia, K. G. Mulyadi (International Journal of Research in Medical Sciences, 2017)
Background: Osteosarcoma progression characterized by the presence of metastasis dan local recurrence. Several studies focused on bone morphogenetic protein-2 (BMP-2) and P-glycoprotein as protein that influence the progression of osteosarcoma, which are characterized by metastasis and local recurrence. Methods: This study was a cross sectional analytic study. This study looks at the relationship level of BMP-2 and P-glycoprotein with metastasis and local recurrence in osteosarcoma. Twenty three research subjects are paraffin blocks of osteosarcoma patients and secondary data was conducted through medical records to determine metastasis and local recurrence that occurs in these patients. Results: The result showed significant correlation between BMP-2 and P-glycoprotein with metastasis and local reccurence. Conclusions: BMP-2 and P-glycoprotein positivity as determined by immunohistochemistry, was a strong correlate of more rapid disease progression. It should be taken into consideration to identify a subgroup of osteosarcoma patients with poor outcome at the time of diagnosis. So it might be an important marker in planning innovative chemotherapeutic regimens.